Elettronica e antropologia. Note su Macchine come me (2019) di Ian McEwan - Amato, Pierandrea (Mechane, 2021)
The paper presents a philosophical reading of a recent novel by British writer Ian McEwan, Machines Like Me (2019), conceived around the moral vicissitudes of an android, Adam, marketed in early 1980s London. The analysis of the novel is an opportunity to reflect around the aesthetic representability of the post-human and the aporias that this temptation implies.